Kesiapan Masyarakat Terhadap Transformasi Digital: Studi Pandangan Masyarakat Terhadap Kurikulum Digital pada Pendidikan Formal dan Nonformal di Pamekasan - Adawiyah, Robiatul; Rohman, Imdadur; Soleh, Badrus (re-JIEM (Research Journal of Islamic Education Management), 2026)
This study analyzes community readiness for digital transformation through perspectives on digital curricula in formal and nonformal education in Pamekasan. Employing a quantitative descriptive approach, data were collected from 55 respondents (aged 13–22 and ≥23) via structured online questionnaires and analyzed using descriptive statistics. Results reveal that 92.7% of respondents consider formal education highly important, with 87.3% viewing it as classroom-centered and 89.1% socially valuing formal credentials more. Conversely, 94.5% acknowledge nonformal education enhances communication skills, 89.1% rate its learning methods as more flexible, and 98.2% recognize it as an inclusive pathway for underprivileged groups. The findings highlight a perceptual dichotomy: formal education is perceived as more structured and prestigious, while nonformal education excels in practical skill development and flexibility. Successful digital curriculum transformation requires strengthened ICT educator competencies, equitable infrastructure, and integrated pedagogical-andragogical approaches. This research offers strategic insights for digital curriculum policy and community empowerment in the digital era.